Hematologic Ratios in Donkeys: Reference Intervals and Response to Experimentally Induced Endotoxemia - Carmen Davias; Francisco J. Mendoza; Adelaida De Las Heras; Carlos Gonzalez-De-Cara; Antonio Buzon-Cuevas; Alejandro Perez-Ecija (Animals)
Endotoxemia is commonly observed in donkeys, secondary to colic, pleuropneumonia, or diarrhea among other disorders. Hematologic ratios are new biomarkers widely used in the diagnosis and prognosis of multiple conditions in human medicine, including sepsis. While the utility of these ratios has been proved in septic foals, no data are available on donkeys. Moreover, reference intervals (RIs) have not been studied in this species. In this study, RIs of the most commonly reported hematologic ratios were determined in 73 healthy adult donkeys. In addition, variations in these ratios in response to LPS infusion were also evaluated in six healthy adult donkeys. Most of the ratios evaluated showed significant variations after induced endotoxemia, with most of them showing values outside of the established RIs. Similarly to septic foals, the neutrophil to lymphocyte ratio was significantly reduced after LPS infusion. No significant changes were observed in the red cell distribution width to platelet ratio, contrary to reports on septic foals. Previously reported cut-off values for both of these ratios should not be extrapolated to donkeys. Future studies evaluating these ratios in natural endotoxemia or other diseases in donkeys, as well as establishing species-specific cut-off values, are necessary.